LEGAL DECONSTRUCTION OF TAX AUDIT ON THE TAX-PAYER’S REFUND APPLICATION FOR TAX OVERPAYMENT IN INDONESIA (PART 2 OF 2) - Henry D.P. Sinaga; Yuli T. Hidayat (Journal of Tax Law and Policy, 2022)
There is still an empirical and philosophical juridical gap in tax audits on Overpayment Tax Returns (SPT) as referred to in Article 17 and Article 17B of the KUP Law. It is necessary to con-duct philosophical research in the field of non-positivistic law with the method of legal deconstruction and use the theory of justice as fairness that John Rawls has put forward in answer-ing the two existing problems. This study yields two conclu-sions. First, legal texts related to Article 17 and Article 17 B of the KUP Law and Regulation of the Minister of Finance Number 17/PMK.03/2013 in conjunction with Regulation of the Minis-ter of Finance Number 184/PMK.03/2015 in conjunction with Regulation of the Minister of Finance Number 18/PMK.03/ 2021 does not meet the theory of justice as fairness to taxpay-ers. Second, it is necessary to carry out legal deconstruction of Article 17B of the KUP Law so that a definitive legal text in tax audits is produced based on the theory of justice as fairness. It is recommended that there be reforms to tax laws and regula-tions related to the provisions on the examination of Overpay-ment Tax Returns (SPT) that take into account the following matters, among others, the abolition of the 12-month audit pe-riod of Overpayment Tax Returns (SPT) while maintaining the same examination period and equal treatment of administrative sanctions in exchange for interest fairly.